Proximate compositions, phytochemical constituents, antioxidant activities and phenolic contents of seed and leaves extracts of Egyptian leek (Allium ampeloprasum var. kurrat) - El-Rehem, Fouad Abd El-Rehem Ahmed Abd; Ali, Rehab Farouk Mohammed (European Journal of Chemistry, 2013)
Leeks (Allium ampeloprasum var. kurrat.) are the most commercially produced vegetables in the world. The seed and leaves of this plant were analyzed for proximate composition and mineral content. Phytochemical screening, total polyphenols, total flavonoids, tannins, radical scavenging activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH), total antioxidant activities and phenolic profile of various extracts of Egyptian leek were screened and investigated. The seed is good source of fat and protein, whereas the leaves are good source of crude fiber and ash. Both seed and leaves contain substantial quantities of potassium, calcium, and phosphorus. Methanolic and ethanolic extracts of seeds and leaves were found to contain alkaloids, steroids, terpenoids, flavonoids, tannins, saponines, reducing sugars, proteins and oil. The highest values of total phenolic, flavonoid, tannin, radical scavenging and antioxidant activities were observed for methanolic and ethanolic extracts of seed and leaves. HPLC analysis results showed that certain phenolic compounds; gallic, coumaric, caffeic, tannic, vanillic, chlorogenic, kaempferol, and quercetin exist in methanolic extracts of both seed and leaves at different levels. These results suggested that Allium ampeloprasum phenolic compounds could be used as a natural antioxidant.